Histopathology : techniques and its management - Nayak, Ramadas (Jaypee, 2018)
This textbook deals with basic histopathology techniques: Introduction and examination of tissue, fixation and fixatives, tissue processing and embedding, decalcification, microtomy and section cutting, frozen section and cryostat, theoretical aspects of staining, hematoxylins and eosin, staining procedure and mounting, demonstration of carbohydrates, pigments and minerals, staining for amyloid, connective tissues stains, stains for lipids, stains for microorganisms, immunohistochemistry, automation in histopathology, museum technique, microscope, photography, biomedical waste & its management and total quality management. This also deals with the management of various problems encountered in histopathology techniques.